Pemodelan Alat Pencegah Micro-Sleep Sebagai Upaya Mitigasi Kecelakaan Transportasi - Sugiharto, Wibowo Harry; Ghozali, Muhammad Imam; Murti, Alif Catur (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Micro-sleep (MS) is a short sleep condition ranging from 1 to 30 seconds, where people who experience this condition fail to respond to motor sensors and become unconscious. Micro-sleep often occurs as a result of lack of sleep, but not always micro-sleep is caused by lack of sleep, some cases explain that micro-sleep sufferers are also experienced by those who do during monotonous work. Micro-sleep becomes very important when this condition involves dangerous conditions. Even though it's only a few seconds, of course this is very dangerous, and may be one of the main causes of accidents. By utilizing sensor technology, we can do realtime monitoring of the data of the owner, so that a tool that can detect the condition of the driver who has micro-sleep can be developed. With this information the micro-sleep detector will make a warning to the driver. This is expected to reduce the number of accidents caused by micro-sleep.